Improvement of Lightning Conductors to Prevent Creeping Discharge - Pathorn Sirachansawang; Surachai Phommeepun; Wiroj Tangtheerajaroonwong; Techatat Buranaaudsawakul; P. Apiratikul; Boonsak Kiatjaroonlert; Werachet Khanngern; Atthapol Ngaopitakkul (My University, 2024)
This research is a test of a lightning conductor that can prevent or reduce the distance from lightning current jumps between the lightning conductor and nearby metal. The lightning conductor must have durable insulation to protect against lightning current jumps to a certain extent. But if the separation distance (s) cannot be maintained, the potential must be coordinated with the lightning conductor to prevent the occurrence of metal arcs. This research will test the ability to protect the separation distance, s = 50 cm. A copper lightning conductor has a cross-sectional area of 50 sq.mm. and the thickness of the electrical insulation is an important part in protecting against a voltage of 600. kV. If there is no insulation to protect the voltage at 600 kV, the ability to jump the lightning current will be at a distance of 50 m. The KHV cable is important for intelligent buildings that have lightning protection systems. It can isolate electrical and electronic equipment and external lightning protection.
Keywords: High voltage insulation and dielectric phenomena; Electromagnetic Launch and Propulsion Technology; Power Transformer Diagnostics and Insulation